Philosophy on tap : pint-sized puzzles for the pub philosopher - Lawrence, Matt, 1963- 4 0 16; 5 (Chichester, West Sussex, UK : Wiley-Blackwell, 2011)
Pairs different beers with forty-eight short philosophical puzzles, each designed to be examined in no more time than it takes to drink a pint.;When beer starts to flow, philosophical discussions naturally follow. Philosophy on Tap takes pub philosophy to the next level, pairing 48 of life's greatest philosophical questions with 48 of the world's best beers. Features a unique presentation of philosophical puzzles, paradoxes, and debates by considering 48 of life's biggest questions in the context of 48 distinctive beers from around the world Provides a highly engaging and sociable approach to the classic philosophical problems as well as a unique look at the conundrums that directly affect the beer drinker Combines a philosopher's insights with thematic humor and trivia to explore issues such as free will, God's existence, the nature of the soul, time travel, the aesthetics of taste, the role of beer in the good life, and the infamous beer goggles paradox For beer drinkers who enjoy philosophy, philosophers who enjoy beer, and anyone who has ever pondered the meaning of life over a pint of ale-- Provided by publisher. Isn't it about time that philosophical discussion is brought out of the classroom and into the local pub? Philosophy on Tap offers revealing insights into 48 of the most perplexing philosophical conundrums by merging the worlds of beer and philosophy. Pairing each philosophical puzzle with a distinctive pint of beer, pub philosophers can ponder the nature of the soul over a Rogue Dead Guy Ale, examine time travel while sipping a Kronenbourg 1664, meditate on nirvana while delighting in a Lhasa Beer of Tibet, or contemplate the meaning of life while quaffing an Abyss Imperial Stout. You can also quench your thirst for philosophical knowledge about the role of beer in the good life, analyze the aesthetics of taste, and get to the bottom of the infamous beer goggles paradox. Philosophy on Tap proves that all the great philosophical puzzles go down much easier when considered through a beer-lover's lens, including such imponderables as Could God make a keg so big that He himself can't lift it? Blending a splash of intoxicating humor with numerous sobering insights, Philosophy on Tap is certain to satisfy both philosophers and beer lovers alike-- Provided by publisher.
Machine generated contents note: 1. Transporter Troubles. 2. Zeno's Hand to Mouth Paradox. 3. If a Pint Spills in the Forest. 4. The Beer Goggles Paradox. 5. Pascal's Wager. 6. The Experience Machine. 7. Lucretius' Spear. 8. The Omnipotence Dilemma. 9. What Mary Didn't Know About Lager. 10. Malcolm X and the Whites Only Bar. 11. Untangling Taste. 12. The Foreknowledge Paradox. 13. The Buddha's Missing Self. 14. The Blind Men and the Black and Tan. 15. Liar's Paradox. 16. Paley's Cask. 17. Chuang Tzu's Butterfly. 18. Descartes' Doubt. 19. God's Command. 20. Mill's Drunkard. 21. The Myth of Gyges. 22. Laplace's Superscientist. 23. Gaunilo's Perfect Ale. 24. The Problem of Moral Truth. 25. How to Sew on a Soul. 26. Plato's Forms. 27. Realizing Nirvana. 28. The Problem of Evil. 29. Time's Conundrum. 30. Time Travel Paradoxes. 31. Hitler's Lager. 32. The Zen Koan. 33. Sex and Sensibility. 34. Socrates' Virtue. 35. Nature Calls. 36. Nietzsche's Eternal Recurrence. 37. The Most Interesting Man and the Firing Line. 38. Turing's Tasting Machine. 39. Singer's Pond. 40. The Wisest One of All. 41. Enter the Matrix. 42. A Case of Bad Faith. 43. Cask and Cleaver. 44. Flirting with Disaster. 45. Fear of Zombies. 46. Lao Tzu's Empty Mug. 47. Beer and the Meaning of Life. 48. The Case for Temperance.
Includes bibliographical references (p. [218-228).
Adult;Adult.
Keywords: 2 -- 0; 6; Philosophy;Bars (Drinking establishments) -- 20 -- Miscellanea.;Miscellanea.; 20; 2